Проблеми правового регулювання дистанційної роботи працівників в умовах пандемії - Коваленко, К. В.; Kovalenko, K. V.; ORCID: http://orcid.org/0000-0002-2105-9664 (Вісник Харківського національного університету внутрішніх справ. – 2021. – № 3 (94). – С. 58-65, 2021)
Аргументовано, спираючись на аналіз наукових поглядів учених та норм чинного законодавства України, що останнім етапом правового регулювання дистанційної зайнятості стало чітке відмежування надомної роботи та дистанційної роботи. Зазначено, що до проблем правового регулювання дистанційної роботи в умовах пандемії доцільно віднести нормативно-правову регламентацію захисту трудових прав під час дистанційної роботи, зокрема питання нормування та оплати праці. Наголошено, що в чинному законодавстві слід визначити групи працівників, зокрема перелік посад посадових осіб, які за специфікою своєї діяльності не можуть працювати дистанційно.

Based on the analysis of scientific views of scholars and current legislation of Ukraine, it has been argued that the announcement of a pandemic and the introduction of measures aimed at limiting public contact have accelerated the normative and legal regulation of remote employment, which has already developed into global quarantine. Teleworking, as well as remote work provided by the Labor Code – are priority forms of remote work in a pandemic, which contribute to the implementation of anti-epidemic measures. It has been emphasized that the last stage of legal regulation of remote employment was a clear distinction between teleworking and remote work. It has been substantiated that the features that distinguish remote work from teleworking should include: first of all, the place of remote work, namely: outside the working premises or territory of the owner or his authorized agency by the employee’s choice; secondly, the mandatory use of information and communication technologies. It has been noted that according to the place of remote work we can distinguish remote work, which is carried out: a) only in a place (places), which is determined by the employee; b) in a place determined by the employee with a combination of the employee’s work at the working place in the premises or on the territory of the owner of the enterprise, institution, organization or its authorize d agency by the agreement between the employee and the owner of the enterprise, institution, organization or authorized agency. It has been generalized that the problems of legal regulation of remote work in a pandemic should include the legal regulation of protecting labor rights during remote work, in particular the issue of rationing and remuneration. It has been emphasized that the current legislation should define groups of employees, including a list of positions of officials who, due to the specifics of their activities, cannot work remotely.

Аргументировано, основываясь на анализе научных взглядов ученых и норм действующего законодательства Украины, что последним этапом правового регулирования дистанционной занятости стало четкое отграничение надомной работы и дистанционной работы. Отмечено, что к проблемам правового регулирования дистанционной работы в условиях пандемии целесообразно отнести нормативно правовую регламентацию защиты трудовых прав во время дистанционной работы, в частности вопросы нормирования и оплаты труда. Отмечено, что в действующем законодательстве следует определить группы работников, в частности, перечень должностей должностных лиц, которые по специфике своей деятельности не могут работать дистанционно.
Problems of Legal Regulation of Employees’ Remote Work in Terms of Pandemic
Коваленко, К. В. Проблеми правового регулювання дистанційної роботи працівників в умовах пандемії / Костянтин Вікторович Коваленко // Вісник Харківського національного університету внутрішніх справ. – 2021. – № 3 (94). – С. 58-65. – DOI: https://doi.org/10.32631/v.2021.3.05.
Коваленко, К. В. (2021) «Проблеми правового регулювання дистанційної роботи працівників в умовах пандемії», Вісник Харківського національного університету внутрішніх справ, 94(3), с. 58-65. doi: 10.32631/v.2021.3.05.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; правове регулювання; дистанційна робота; пандемія COVID-19; трудове законодавство; правовое регулирование; дистанционная работа; пандемия; трудовое законодательство; legal regulation; remote work; pandemic; labor legislation; пандемія